OVERVIEW OF THE STATUS AND TRENDS OF RESEARCH ON THE RISKS OF THE USE OF CLOUD TECHNOLOGIES - KULAKOVSKA, INESSA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Cloud technologies have become an integral part of today’s digital world, offering many advantages for businesses and private users. Their flexibility, scalability, and cost-effectiveness make them an attractive choice for data storage, software development, and other IT services. However, along with the advantages, cloud technologies also carry certain risks that cannot be ignored. The study of these risks is extremely urgent. Cloud technology provides on-demand services over the Internet using a large amount of virtual storage. The main features of cloud solutions are that the user does not configure the computing infrastructure, and the cost of services is lower. In recent years, cloud computing has been integrated with industry and many other fields, encouraging the exploration of new related technologies and AI. Due to the availability of cloud services and scalability for computing processes, individual users and organizations are transferring their applications, data and services to a cloud storage server. Despite its advantages, the transformation of on-premises computing to remote computing has brought many security issues and challenges for both the consumer and the provider. Many cloud services are provided by a third party, which creates new security threats. The cloud provider provides its services over the Internet and uses many web technologies, which creates security problems here as well. The study examines the main features of cloud technologies, security issues, potential threats and their solutions. Six key topics related to cloud security, cloud architecture framework, service and deployment models, cloud technologies, cloud security concepts, threats and attacks are described. The paper also discusses many open research questions related to risk assessment methods for each of the cloud vulnerabilities. Dependence on cloud services is constantly growing, because more and more companies and organizations are switching to their use. This makes them more vulnerable to disruptions, cyber-attacks and other problems that can lead to significant data loss, financial losses and reputational losses.